20-HETE and CYP4A2 ω-hydroxylase contribute to the elevated blood pressure in hyperandrogenemic female rats - Dalmasso, Carolina (Am J Physiol Renal Physiol, 2016)
In male rats, androgen supplements increase 20-hydroxyeicosatetraenoic acid (20-HETE) via cytochrome P-450 (CYP)4A ω-hydroxylase and cause an increase in blood pressure (BP). In the present study, we determined the roles of 20-HETE and CYP4A2 on the elevated BP in hyperandrogenemic female rats. Chronic dihydrotestosterone (DHT) increased mean arterial pressure (MAP) in female Sprague-Dawley rats (96 ± 2 vs. 108 ± 2 mmHg, P < 0.05) and was associated with increased renal microvascular CYP4A2 mRNA expression (15-fold), endogenous renal 20-HETE (5-fold), and ω-hydroxylase activity (3-fold). Chronic DHT also increased MAP in low salt-fed Dahl salt-resistant female rats (81 ± 4 vs. 95 ± 1 mmHg, P < 0.05) but had no effect on MAP in Dahl salt-sensitive female rats (154 ± 3 vs. 153 ± 3 mmHg), which are known to be 20-HETE deficient. To test the role of CYP4A2, female CYP4A2(−/−) and SS.5(Bn) (wild type) rats were treated with DHT. DHT increased MAP in SS.5(Bn) female rats (104 ± 1 vs. 128 ± 1 mmHg, P < 0.05) but had no effect in CYP4A2(−/−) female rats (118 ± 1 vs. 120 ± 1 mmHg). Renal microvascular 20-HETE was reduced in control CYP4A2(−/−) female rats and was increased with DHT in SS.5(Bn) female rats (6-fold) but not CYP4A2(−/−) female rats. ω-Hydroxylase activity was 40% lower in control CYP4A2(−/−) female rats than in SS.5(Bn) female rats, and DHT decreased ω-hydroxylase activity in SS.5(Bn) female rats (by 50%) but significantly increased ω-hydroxylase activity in CYP4A2(−/−) female rats (3-fold). These data suggest that 20-HETE via CYP4A2 contributes to the elevation in BP in hyperandrogenemic female rats. The data also suggest that 20-HETE synthesis inhibition may be effective in treating the elevated BP in women with hyperandrogenemia, such as women with polycystic ovary syndrome.